ANALISIS KESALAHAN MAHASISWA PGSD DALAM MENYELESAIKAN MASALAH GEOMETRI - A. Wilda Indra Nanna; Enditiyas Pratiwi; Cahyo Anggraeni (Prodi Pendidikan Matematika FKIP Universitas Madura, 2020)
One of the courses have often difficult by pre service teacher in primary education is Geometry, evidently by learning outcome that are still low. Difficulties experienced by students led to an error occurred in solving problem in geometry. Errors that occur when students solve problems in geometry really need to be known, especially the type of error. One of procedure that can be used to reveal the student error is Newman procedure. This research employed a descriptive qualitative method that aimed to analyze the errors of pre service teacher in primary education when solve the problems in geometry. Participants in this research were two students who have taken the courses of Geometry and meet the criteria which is experiencing a mathematical error. Data collection technique use a question sheet and interviews. Question sheet given in order to analyze student errors that appear. While the interviews were conducted to confirm the results of student work. The results showed that the four stages of the procedure of Newman Error Analyze that comprehension, transformation, process skill and encoding occur mathematical error, logical error and strategic error. Furthermore, as new findings in this research, the error experienced by the students at this stage of the procedure Newman can cause errors in the later stages.